A unified formulation of RMVT-based finite cylindrical layer methods for sandwich circular hollow cylinders with an embedded FGM layer - Wu, Chih-Ping; Chang, Yu-Tsao (Composites. Part B, Engineering, 2012)
A unified formulation of finite cylindrical layer methods (FCLMs) based on the Reissner mixed variational theorem (RMVT) is developed for the quasi-three-dimensional (3D) analysis of simply-supported, multilayered composite cylinders and sandwich circular hollow cylinders with an embedded functionally graded material (FGM) cylindrical layer, subject to mechanical loads. The material properties of the FGM layer are assumed to obey an exponent-law varying exponentially with the thickness coordinate. In this formulation, the circular hollow cylinder is divided into a number of finite cylindrical layers, in which the trigonometric functions and Lagrange polynomials are used to interpolate the in- and out-of-surface variations of the field variables of each individual layer, respectively. Because an h-refinement instead of a p-refinement process is adopted to yield the convergent solutions in this work, the layerwise linear, quadratic or cubic function distribution through the thickness coordinate is assumed for the related field variables. The accuracy of the FCLMs developed in this article is assessed by comparing their solutions with the exact 3D ones available in the literature, and the convergence rate and possibility of numerical instability of these FCLMs are also investigated.